2003
DOI: 10.1053/eupc.2002.0272
|View full text |Cite
|
Sign up to set email alerts
|

Effect of biventricular pacing on metabolism and perfusion in patients affected by dilated cardiomyopathy and left bundle branch block: evaluation by positron emission tomography

Abstract: Our results suggest that, in patients affected by DC and LBBB, BIVP improves the septal glucose metabolism without significant changes in myocardial perfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 9 publications
3
46
0
Order By: Relevance
“…170 By reduction of the inefficiency of dyscoordinate ventricular contractions, cardiac resynchronization therapy increases glucose metabolism and reduces IR 171,172 to improve cardiac efficiency and cardiac energetics. [173][174][175][176] Statins lessen the incidence of new diabetes in patients with metabolic syndrome, 175 improve glucose tolerance, 177,178 and improve HF.…”
Section: Other Potential Therapiesmentioning
confidence: 99%
“…170 By reduction of the inefficiency of dyscoordinate ventricular contractions, cardiac resynchronization therapy increases glucose metabolism and reduces IR 171,172 to improve cardiac efficiency and cardiac energetics. [173][174][175][176] Statins lessen the incidence of new diabetes in patients with metabolic syndrome, 175 improve glucose tolerance, 177,178 and improve HF.…”
Section: Other Potential Therapiesmentioning
confidence: 99%
“…22,23 Nowak et al suggested that restoration of septal glucose uptake after CRT, as reflected by FDG uptake, was in accordance with an increase of GLUT-4 because of the increase in workload. 19 In a previous report, 24 glucose metabolism in the septum improved with less alteration in perfusion subsequent to CRT, so the restoration of glucose metabolism after CRT may be caused by an alteration in septal workload, and not by restoration of perfusion. The mechanism of the reverse mismatch in LBBB may be the result of reduced septal workload with reduced expression of GLUT-4.…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies characterized global MVO 2 and MBF in cardiomyopathy with PET, they failed to discriminate between LBBB and non-LBBB patients [17][18][19][20][21]. Recent studies that focused on regional aspects of LBBB on a semiquantitative or quantitative basis mostly of the septal and the lateral walls included only a small number of patients [22][23][24][25][26]. To our knowledge, the present study is the first one to quantitatively investigate both global and regional MVO 2 as well as global and regional MBF in a larger DCM population.…”
Section: Discussionmentioning
confidence: 99%
“…The rationale is to reduce the LBBB associated intraventricular dyssynchrony in DCM patients by synchronous biventricular pacing. Correspondingly, PET investigations revealed that regional inhomogeneities of glucose metabolism, MVO 2 and MBF were balanced [22][23][24][25][26].…”
Section: Regional Mvo 2 and Mbf In Dcm Patients With And Without Lbbbmentioning
confidence: 99%